2018
DOI: 10.1021/acs.chemmater.7b04849
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Poly(3-hexylthiophene) (P3HT) Doped with 2,3,5,6-Tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) by Vapor-Phase Infiltration

Abstract: Doping of thin films of semiconducting polymers provides control of their electrical conductivity and thermopower. The electrical conductivity of semiconducting polymers rises nonlinearly with the carrier concentration, and there is a lack of understanding of the detailed factors that lead to this behavior. We report a study of the morphological effects of doping on the electrical conductivity of poly­(3-hexylthiophene) (P3HT) thin films doped with small molecule 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
227
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(254 citation statements)
references
References 65 publications
(170 reference statements)
22
227
5
Order By: Relevance
“…As the magnitude of the bias increases, the alkyl stacking distance increases sharply to 18.5 Å (Figure c) along with a decrease in π–π stacking distance to 3.62 Å (Figure d). The structural changes observed suggest that the TFSI − counterions reside in the alkyl chains of the crystallites, consistent with other dopant molecules used for P3HT . As expected, the positions of the scattering peaks of the PIL (P1, P2, and P3) are not influenced by application of a gate bias.…”
Section: Resultssupporting
confidence: 83%
“…As the magnitude of the bias increases, the alkyl stacking distance increases sharply to 18.5 Å (Figure c) along with a decrease in π–π stacking distance to 3.62 Å (Figure d). The structural changes observed suggest that the TFSI − counterions reside in the alkyl chains of the crystallites, consistent with other dopant molecules used for P3HT . As expected, the positions of the scattering peaks of the PIL (P1, P2, and P3) are not influenced by application of a gate bias.…”
Section: Resultssupporting
confidence: 83%
“…We also found that most of the experimental results for P3HT are within the range of ≈10 −1 –10 2 µW m −1 K −2 , located within our calculated orders of magnitude. It is worth noting that very few experimental work can directly measure the free carrier concentration of a polymer sample, and several reports showed that their measured carrier concentrations are about 10 21 cm −3 , [ 24,31 ] higher than our predicted optimal doping level (1 × 10 20 –5 × 10 20 cm −3 ), which obviously are over‐doped. Therefore, direct comparison of the absolute value of power factor in the case of unknown carrier concentration is pointless; however, the trend and range of values are meaningful and crucial.…”
Section: Figurecontrasting
confidence: 56%
“…For example, the mobility of P3HT:F4TCNQ films increases from around 0.2–0.9 cm 2 V −1 s −1 when the carrier concentration increases from 2 × 10 19 to 5 × 10 20 cm −3 . [ 24 ] Such phenomenon can be attributed to the easy trapping of the charge carriers by counterions at low concentrations due to the strong electrostatic attractive interactions. However, a portion of carriers can fill the traps at higher concentrations, and thereby the remaining carriers undergo the trap‐free transport.…”
Section: Figurementioning
confidence: 99%
“…[21,22] To date, CQD thermoelectrics have been reported with advanced performance approaching that of conventional bulk Bi 2 Te 3 -based systems. While p-type films [17,[28][29][30][31] have seen rapid advancement, the thermoelectric performance of n-type counterparts still lags behind. [16,19,20] Film-based CQD structures offer the potential for micropower applications such as self-powered devices in sensor networks and the internet of things.…”
mentioning
confidence: 99%